Examining "best practices" for literacy coaching and monitoring: Evidence from Northern Nigeria and Ghana. Issue 1 (2020) - Smiley, Anne; Cao, Yvonne; Moussa, Wael; Dooley, Brian; Sullivan, Jane
Abstract: Evidence-based 'best practices' from high-resource contexts have motivated some early grade literacy programs in developing countries to hire private literacy specialists as coaches for teachers, rather than build coaching into the job description of existing system actors, such as school inspectors. This study poses the question, can education system actors with supervisory responsibilities for schools, who are not necessarily literacy specialists, become effective literacy coaches? Using secondary data from a reading program in Nigeria, we use a fixed-effects regression framework to evaluate the relative effectiveness of external subject matter experts and system actors on teaching and learning outcomes. We find that in Nigeria, system actors are as effective at improving both program implementation and teacher performance as externally hired reading experts. Qualitative data from contrasting coaching models in Nigeria and Ghana provide insight into the reasons why school inspectors may be well-suited for coaching.